High performance technique FIR Filter Using Least Squares Method - Haitham Abbood, Wisam (Journal of Engineering and Sustainable Development, 2008)
The FIR filter is the one from the most DSP components used. There are two main approaches to design of FIR, first using the windows that have simple mathematics calculations but its results are not optimal. The second method that uses Least Squares error approach to get an optimal design but it required to large number of calculations.A new algorithm for weighted least squares linear-phase FIR filter design has been presented, this algorithm used to solve quadratic programming problems. This paper shows how to rearrange this algorithm to reduce the number of flouting point operations (FPOs), that will results in a faster method for constrained least squares FIR filter design. The proposed algorithm is fast, stable and suitable for high order filter design.